Electrocaloric materials and applications based on multilayer ceramic capacitors - Li-Qian Cheng; Yongke Yan; Zhiping Wang; Zhengyu Li; Xiaotian Li (Journal of Materiomics, 2025)
The increasing demand for effective and environmentally compatible cooling technologies has driven significant interest in the development of solid–state cooling materials. Among these, the electrocaloric (EC) system is considered a promising solid–state cooling method, offering advantages over other cooling technologies, such as low environmental impact, cost–effectiveness, high energy efficiency, and compact device size. To fully harness the potential of EC materials, multilayer ceramic capacitors (MLCCs) have emerged as effective and appropriate structures for EC cooling applications. This article provides a comprehensive review of recent advancements and research trends in MLCC–based EC materials, including the fundamentals of the EC effect, the performance of MLCC–based EC materials, EC effect (ECE) measurement, multilayer geometric structure design, and cooling device design based on MLCCs. A comparison of different systems of EC materials, along with an exploration of microstructure improvement, was conducted based on recent studies. A special focus was placed on multilayer structure design for EC performance enhancement, followed by reviewing two types of EC cooling device designs. The review offers insights into the fabrication and characterization of MLCC–based EC materials, offering guidance for future developments in EC material research and practical applications.